The alternative new media and democratic participation in Malaysia: opportunities and challenges - Ahmad Ishak, M.S. (2009)

(untitled)
This paper examines how Malaysian civil societies have explored the use of new media technology, particularly the Internet, to promote the freedom of expression and participation in local democratic processes. The analytical discussions attempt to shed light on several questions. What are the opportunities and limitations of new media as a civic tool? What has been the impact on freedom of expression so far? What have been the problems? What are the possible future directions and concerns? Discussion of these questions is structured into several parts. The first part introduces the definitions and scope of new media and other concepts as well as theoretical potentials of using new media in civil society. The second section sets the Malaysian scene with a brief survey of the news portals as the alternative media in Malaysia with an analysis of government and the media. The concluding section analyses the use of new media and its relation with democratic participation, and examines the problems arising from this development.